STRUCTURAL DESIGN OF THE MODEL CYCLONE FOR UTILIZATION IN THE EDUCATIONAL PROCESS - PLANDOROVA, Katarina; CERNECKY, Jozef (Trends in education, 2010)
The present contribution deals with structural design of the model cyclone as didactic tool for students with technical focus, as well as for exploitation in the educational process. There must be considered all of the factors in the design of cyclone which have an important weight for structural design and for mean value of separation too. Student can practice measurements on this cyclone in different modes of separation by predetermined methods and procedures.
Keywords: separation; cyclone; structural design.